Desenvolvimento e validação de metodologia analítica para avaliação de ebastina e cloridrato de pseudoefedrina em cápsulas - Delgado, Leila Schreiner (2011)
Ebastine is a second generation antihistaminic clinically used for the treatment of allergic rhinitis and chronic urticaria. Pseudoephedrine hydrochloride is a direct- and indirectacting sympathomimetic, commonly combined with other drugs for their decongestant effect. In Brazil, this drugs association is available in capsules. In the literature, as well as in the official compendium, there are no methods for simultaneous analysis of ebastine and pseudoephedrine hydrochloride in pharmaceutical formulations. In the present work, liquid chromatography (HPLC) and derivative spectrophotometry (UVD) methods were developed and validated for quantification of this drugs association, in capsules. The HPLC analysis were performed on a C18 column, using a mobile phase composed of methanol: acetonitrile: ammonium acetate buffer pH 6.8 (85:5:15, v/v), run at a flow rate of 1,0 mL.min-1, with UV detection at 254 nm. In the UVD method, ebastine was quantified in the first derivative (dA/dλ), at 263.5 and 252.8 nm, respectively. All of them were validated in the following parameters: linearity, precision and accuracy. The specificity was evaluated in the HPLC assay by stress testing. The methods showed good linarity (r>0.99), precision (RSD<2%) and accuracy; the results, statistically compared, did not show significant difference (p>0,05).